Material didáctico innovador para el desarrollo del pensamiento lógico matemático en la Escuela Dr. Fray Pedro Rodríguez de Aguayo, Paltas 2024 - Narváez Cañar, Sandra Elizabeth (2024)
This paper aims at understanding the innovative didactic material for the development of mathematical logical thinking. Its general objective was to analyse the incidence of the innovative didactic material through a pedagogical proposal in the development of mathematical logical thinking in the Dr. Fray Pedro Rodríguez de Aguayo School, Paltas 2024. To reach this general objective, three specific objectives were set: First, to diagnose the levels of mathematical logical thinking presented by the students during their learning process; second, to design a pedagogical proposal that uses innovative didactic material to strengthen students’ mathematical logical thinking; and, third, to apply the pedagogical proposal with innovative didactic material to improve students’ mathematical logical thinking. This research was of a qualitative and quantitative approach, and a descriptive-explanatory type, since it enabled the understanding of the problem regarding the use of didactic materials for the development of mathematical logical thinking; the design applied in this research was quasi- experimental, also, methods such as: Hermeneutic, inductive, deductive, analytical, synthetic, as well as statistical were applied, the techniques that were applied in the research to obtain the information were the pre and post evaluation to self-evaluation; as an instrument, we used the pre-post evaluative questionnaire for data collection, we also worked with non-probabilistic sampling by convenience which comprised 6 students and a teacher. Based on the results, it is concluded that the use of didactic material is positive and contributes to the development of mathematical logical thinking, since experimentation with concrete material improves the teaching-learning process, as it allows the student to better understand the concepts, develop practical skills, increase their motivation and participation in what they are learning, which helps to stimulate their logical reasoning.